MACROECONOMIC ANALYSIS OF INFLATION: EVIDENCE FROM EASTERN INDONESIA - Runtunuwu, Prince Charles Heston; Hussin, Hanafi (JURNAL ECONOMICA : Research of Economic And Economic Education, 2024)
This study aims to determine the money supply, interest rates and exchange rates against inflation. This research data uses secondary data with the time series method obtained from the North Maluku Bank Indonesia (BI) and North Maluku Central Statistics Agency (BPS) from 2010-2020. The method used in this research is multiple linear regression. Based on the results of the study showed that the simultaneous testing showed that of the three variables, there was no effect. Based on the above findings that inflation is mostly influenced by interest rates, if interest rates rise it will increase inflation. Because interest rates have the most dominant contribution in increasing inflation, therefore the monetary authority must try to maintain interest rates for inflation stability.